IMPLENTASI PROGRAM TRANSAKSI ANTAR JEMPUT ANTAR KAMPUNG( TANJAK ) DI KOTA PEKANBARU - Naufal Mahran; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Regional Revenue Agency (Bapenda) of Riau Province has adopted an innovation from West Java Province called Samsat GENDONG to make it easier for taxpayers to pay Motor Vehicle Tax, the name of the program is Samsat Transaction Pickup Between Kampungs (TANJAK). The TANJAK Samsat program is a tax payment service that does not have to come directly to the Samsat office, but this program picks up taxes from the taxpayer and makes it easier for taxpayers who live in the suburbs of Pekanbaru to pay the annual Motor Vehicle Tax (PKB). The purpose of this study is to describe and analyze the implementation of the Samsat TANJAK program and identify and analyze the inhibitory factors of the implementation of the Samsat TANJAK program in Pekanbaru City. The study used the theory of Charles O. Jones uses three indicators: Organization, Interpretation, and Application. The methods used in this study are qualitative research methods that are descriptive. With data collection techniques, observation interviews and documentation. The implementation of the TANJAK Samsat program carried out by the Riau Provincial Bapenda and run by every UPT, especially in Pekanbaru City, has not run optimally and maximally. This is because some of the factors that make the implementation process of the Samsat TANJAK program not optimal and maximum because the facilities and infrastructure provided by Bapenda are still less than sufficient, the socialization carried out by the Riau Provincial Bapenda was left to every UPT implementing the Samsat TANJAK program not adequately However, the lack of regulations specific to implementing the TANJAK Samsat program made the program in implementation less optimal. So that the implementation process of the Samsat TANJAK program can run optimally and maximally, then the above various factors and needs must be improved and implemented to achieve an optimal and more optimal program. Keywords : Implementation, Policy Implementation, Program, Samsat TANJAK.